BIMBINGAN BUDAYA KERJA DALAM PENGUATAN KESEHATAN MENTAL KARYAWAN STUDI KASUS DI CV. BINTANG MANDIRI BANDUNG - Esa Firnanda; Dindin Solahudin; Dono Darsono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Work culture is an important aspect in creating an organizational environment that not only supports the achievement of organizational goals but also promotes employees’ mental health. This study was motivated by the phenomenon observed at CV. Bintang Mandiri Bandung, where employees demonstrate strong loyalty, harmonious working relationships, and relatively positive psychological conditions despite high operational demands. This study aims to describe the process through which work culture is formed through social interaction, analyze how employees interpret work culture in relation to the strengthening of mental health, and examine its implications for Islamic Guidance and Counseling. This study employed a qualitative approach using a case study method. Data were collected through participant observation, in-depth interviews with 14 purposively selected informants, and documentation. Data were analyzed through organization, reduction, presentation, and interpretation processes, supported by source and technique triangulation. The analysis employed George Herbert Mead’s Symbolic Interaction Theory, Edgar H. Schein’s Organizational Culture Theory, the concept of Workplace Mental Health, and the perspective of Islamic Guidance and Counseling. The findings indicate that work culture is formed through continuous social interactions between leaders and employees through role modeling, open communication, briefings, evaluations, positive behavioral habituation, spiritual activities, and interpersonal relationships. These processes foster shared meanings that develop into organizational values, practices, and collective identity. Employees perceive work culture as a source of psychological safety, social support, psychological well-being, psychological resilience, a sense of belonging, and meaningful work, reinforced by spiritual practices. From the perspective of Islamic Guidance and Counseling, work culture performs developmental, preventive, preservative, and curative functions through guidance processes that occur naturally within organizational life. This study contributes a conceptual framework demonstrating that work culture can function as a guidance ecosystem integrating organizational culture, mental health, and Islamic values, resulting in the S.H.O.L.E.H. Work Culture Guidance Model as a development of Islamic Guidance and Counseling in the workplace setting.